Metastatic melanoma response to combination therapy with ipilimumab and vemurafenib - Sachpekidis, Christos; Hassel, Jessica C.; Dimitrakopoulou-Strauss, Antonia (Hellenic journal of nuclear medicine, 2017)
Combination therapies for the treatment of metastatic melanoma are a matter of debate nowadays. We report on a stage IV metastatic melanoma patient with the BRAF V600 mutation and a large tumor burden initially treated with two cycles of ipilimumab. Due to dramatic disease progression, demonstrated on interim 18F-FDG PET/CT, vemurafenib was added in the patients therapeutical scheme. After completion of the concurrent ipilimumab and vemurafenib administration, a third 18F-FDG PET/CT showed an impressive metabolic remission of the metastatic disease, reflecting the potential role of the modality in treatment response evaluation of melanoma patients receiving combination therapies.
DOI lässt sich nicht aufrufen/05.06.2018
Gesehen am 05.06.2018